Pemetaan Status Unsur Hara Fosfor Perkebunan Kelapa Sawit Rakyat di Kelurahan Babat Sumatera Selatan - Bagus Iswahyudi; Bakri Bakri (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Iswahyudi et al, 2019.Â Oil Palm Plantationâ€™s Phosporous Mineral Mapping on Babat District South Sumatera. JLSO 8(1):77-85.Â Soil nutrient status mapping was not initiated which lead to inefficiency in fertilization. Fertilizition without nutrient analysis could lead to nutrient deficiency or toxicity of nutrint. The Purpose of this research was to identify, map the nutrient status and fertilization recomendation of phosporous nutrient status in public oil palm plantation at Babat Village Babat Toman Districts Musi Banyuasin District South Sumatera Province. This research used a detailed survey methode with grid system for 16 sample which represent 16 ha and 60 cm depth of soil drilling. Phosporous nutrient status at research location ranged from 4,81 ppm to 21,86 ppm. 7 ha contained 8-20 ppm available phosphorous ot classified into medium, 6 ha contained < 8 ppm available phosphorous or classified into low and 3 h contained >20 ppm available phosporous or classified into high. Soil reaction (pH) of the research field was 5,0 and 5,5 which classify the soil into acid soil. Fertilization implemented to increase the nutrient status until medium (15 ppm) which resulted in SP-36 doses was 346,22 kg/ha for low nutrient status and 139,33 kg/ha for medium nutrient status.